2003
DOI: 10.1016/s0012-1606(03)00331-2
|View full text |Cite
|
Sign up to set email alerts
|

Tight regulation of SpSoxB factors is required for patterning and morphogenesis in sea urchin embryos

Abstract: Previous studies in sea urchin embryos have demonstrated that nuclearization of beta-catenin is essential for initial steps in the specification of endoderm and mesenchyme, which are derived from vegetal blastomeres. This process begins at the 4th and extends through the 9th cleavage stage, an interval in which the SpSoxB1 transcription regulator is downregulated by beta-catenin-dependent gene products that include the transcription repressor SpKrl. These observations raise the possibility that SpSoxB1 removal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 32 publications
7
54
0
Order By: Relevance
“…This appears to be the case, given that SoxB1 is successively down-regulated in all endomesoderm cell lineages except the foregut as they commit to specific fates: first skeletogenic mesenchyme (21), then nonskeletogenic mesoderm (21-23), and then midgut and hindgut (this study). This pattern of early ubiquitous SoxB1 expression followed by down-regulation through cell signaling is similar to that of the apparent SoxB1 ortholog Sox2 (19,21,24,25), whose role in maintaining pluripotency in mouse embryonic and induced pluripotent stem cells is now well established (26,27). The other SoxB1 class factors, Sox1 and Sox3, also maintain neural progenitors in an undifferentiated state, and their removal is also required for neural differentiation (17,18).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…This appears to be the case, given that SoxB1 is successively down-regulated in all endomesoderm cell lineages except the foregut as they commit to specific fates: first skeletogenic mesenchyme (21), then nonskeletogenic mesoderm (21-23), and then midgut and hindgut (this study). This pattern of early ubiquitous SoxB1 expression followed by down-regulation through cell signaling is similar to that of the apparent SoxB1 ortholog Sox2 (19,21,24,25), whose role in maintaining pluripotency in mouse embryonic and induced pluripotent stem cells is now well established (26,27). The other SoxB1 class factors, Sox1 and Sox3, also maintain neural progenitors in an undifferentiated state, and their removal is also required for neural differentiation (17,18).…”
Section: Discussionsupporting
confidence: 51%
“…We propose that SoxB1 function supports retention of pluripotency in this region, at least in part by antagonizing canonical Wnt signaling that drives endomesoderm development. Previously, we showed that SoxB1 suppresses β-catenin activity in normal embryos during the period when early endoderm is specified and Six3 expression begins, and that misexpression of SoxB1 can completely block endomesoderm development (19). Thus, persistent SoxB1 expression specifically in the foregut could delay progression to a stable endodermal fate, which precludes neurogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Two logical consequences follow from these observations. First, since SoxB1 is cleared from the endomesoderm during the blastula stage, which is a prerequisite for endomesodermal development to proceed (Kenny et al, 1999(Kenny et al, , 2003, its target genes can only be expressed at normal levels in ectodermal, CB, or apical domain cells. This provides a spatial constraint on the expression of SoxB1 target genes adjacent to CB subdomains 3 and 4, both of which abut the Veg1 endoderm.…”
Section: Nanostring Perturbation Analysismentioning
confidence: 99%
“…Many of the transcription factors expressed in the sea urchin embryo ANE (Kenny et al, 2003;Wei et al, 2009) are also expressed in the ectodermal layer of the cnidarian Nematostella vectensis [e.g. six3, hbn, rx, otx, soxb1, soxb2 (Marlow et al, 2009)].…”
Section: Roles Of Canonical Wnt and Tgf Signaling In Positioning Antmentioning
confidence: 99%